Anglo-Saxon Keywords - Frantzen, Allen J., 1947- (Hoboken : John Wiley & Sons, 2012)
Anglo-Saxon Keywords presents a series of entries that reveal the links between modern ideas and scholarship and the central concepts of Anglo-Saxon literature, language, and material culture. Reveals important links between central concepts of the Anglo-Saxon period and issues we think about today. Reveals how material culture--the history of labor, medicine, technology, identity, masculinity, sex, food, land use--is as important as the history of ideas. Offers a richly theorized approach that intersects with many disciplines inside and outside of medieval studies.
Nature; Norman Conquest; O; Orality; P; Paganism; Peace; Peace-weaver; Penance; Piety; R; Race; Recreation; Reform; Rome; S; Scandinavia; Settlement; Sex; Slavery; T; Technology; Thegn; Trade; Tradition; Translation; Trifunctional model; V; Viking; W; War; Works Cited; Index.
Includes bibliographical references and index.
Print version record.
Keywords: 450 - 1100; English language -- Old English, ca. 450-1100 -- Glossaries, vocabularies, etc; English language -- Etymology; Linguistic change; Historical linguistics; English language -- Old English, ca. 450-1100 -- Glossaries, vocabularies, etc; English language; English language -- Etymology; English language -- Old English; Historical linguistics; Linguistic change; Electronic books; Glossaries, vocabularies, etc